Activation of Toll‐like receptors alters the microRNA expression profile of keratinocytes. Issue 4 (April 2014) - Meisgen, Florian; Xu Landén, Ning; Bouez, Charbel; Zuccolo, Michela; Gueniche, Audrey; Ståhle, Mona; Sonkoly, Enikö; Breton, Lionel; Pivarcsi, Andor
Abstract Keratinocytes recognize invading pathogens by various receptors, among them Toll‐like receptors (TLRs), and provide the first line of defense in skin immunity. The role of microRNAs in this important defense mechanism has not been explored yet. Our aim was to identify microRNAs involved in the innate immune response of keratinocytes. MicroRNA expression profiling revealed that the TLR2 ligand zymosan, the TLR3 ligand poly(I:C) or the TLR5 ligand flagellin significantly altered the microRNA expression in keratinocytes. The regulation of microRNAs was concentration‐dependent and it could be neutralized by siRNAs specific for TLR2, TLR3 and TLR5, respectively, confirming the specificity of the TLR response. Interestingly, one microRNA, miR‐146a, was strongly induced by all studied TLR ligands, while other microRNAs were regulated in a TLR‐ or time point‐specific manner. These findings suggest an important role for microRNAs in the innate immune response of keratinocytes and provide a basis for further investigations.